(untitled) (Research, Society and Development, 2023)
Objective: The objectives of this review are to describe the primary and most current findings and neuroimaging exams of the substantia nigra and nigrostriatal pathway in Parkinson’s disease using different imaging methods, in addition to comparing the favorable and unfavorable results of each study and technique. Methodology: Integrative review using the PubMed database during the period of April 2022, with only articles in the English language and published in the last four years (2018-2022) using the following descriptors “Black substance,” “Parkinson’s disease” and “Neuroimaging.” Results: 9 articles were selected for analysis in this work, and among these, five imaging techniques aimed at the substantia nigra and nigrostriatal pathway could be discussed, with three variations of magnetic resonance imaging (MRI) techniques, 1 of Transcranial Ultrasound (TCS) and one cerebral scintigraphy with trodat (Pet or Spec with Trodat). In all studies, excellent results were obtained in terms of accuracy, precision, specificity, and sensitivity. Four of these presented Areas under the Curve above 0.900 and samples ranging from 56 to 3123. Conclusion: The studies analyzed in this review demonstrated consistent and relevant advances in imaging exam options for early diagnosis in PD and evolutionary follow-up of changes related to NS and the nigrostriatal pathway. Neuroimaging techniques have aroused the scientific community’s interest in recent years, with great potential, which will provide relevant knowledge for treating this disease, contributing to a better prognosis for patients.